Penerapan Relaksasi Genggam Jari dan Nafas Dalam pada Pasien dengan Hipertensi - Nur Rizki , Anna; Clara, Hertuida (Neolectura, 2026)
Hypertension, known as the silent killer, is a global health problem with a high prevalence rate. Hypertension needs to be treated seriously to prevent complications. The purpose of this study was to apply nursing care and finger grip and deep breathing relaxation techniques to hypertensive patients using a comprehensive nursing process approach. This study used a descriptive method with a case study approach accompanied by the application of evidence-based practices. Nursing care was provided to a 57-year-old female patient with a medical diagnosis of hypertension. The assessment revealed four nursing problems, namely risk of decreased cardiac output, acute pain, risk of nutritional deficiency, and activity intolerance. The implementation carried out for the nursing problem of risk of decreased cardiac output included performing finger grip relaxation and deep breathing techniques. The evaluation results showed a decrease in blood pressure from 211/100 mmHg on the first day to 152/76 mmHg on the third day. Nurses can teach finger grip relaxation and deep breathing techniques to patients and families to lower blood pressure.